2012
DOI: 10.1371/journal.pone.0035259
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of an Odorant Receptor OR7D4 and Sensory Perception of Cooked Meat Containing Androstenone

Abstract: Although odour perception impacts food preferences, the effect of genotypic variation of odorant receptors (ORs) on the sensory perception of food is unclear. Human OR7D4 responds to androstenone, and genotypic variation in OR7D4 predicts variation in the perception of androstenone. Since androstenone is naturally present in meat derived from male pigs, we asked whether OR7D4 genotype correlates with either the ability to detect androstenone or the evaluation of cooked pork tainted with varying levels of andro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 21 publications
(38 reference statements)
4
45
0
Order By: Relevance
“…We and others showed previously that the intensity perception of androstenone and androstadienone—the two most variably perceived stimuli in our study—is altered by genetic variation in the odorous steroid-sensitive odorant receptor OR7D4 [19,21,23]. Here we show in the same subject population that androstadienone was perceived to be stronger by older subjects (Figure 5d) and women (Figure 5e).…”
Section: Resultssupporting
confidence: 76%
“…We and others showed previously that the intensity perception of androstenone and androstadienone—the two most variably perceived stimuli in our study—is altered by genetic variation in the odorous steroid-sensitive odorant receptor OR7D4 [19,21,23]. Here we show in the same subject population that androstadienone was perceived to be stronger by older subjects (Figure 5d) and women (Figure 5e).…”
Section: Resultssupporting
confidence: 76%
“…In one recent study, anstrostenone-containing meat was found to be less acceptable to subjects with two copies of the RT variant of the OR7D4 receptor, indicating that this genetic variation affects food preferences (Lunde, et al, 2012). The existence of this taint in pork is already a particular problem for pork producers, and one that may become may become more worrisome in Europe, where a proposed ban on pig castration due to animal cruelty issues could lead to a rise in androstenone levels in pork, and subsequently reduce consumer acceptance.…”
Section: Odormentioning
confidence: 99%
“…The existence of this taint in pork is already a particular problem for pork producers, and one that may become may become more worrisome in Europe, where a proposed ban on pig castration due to animal cruelty issues could lead to a rise in androstenone levels in pork, and subsequently reduce consumer acceptance. In Norway for example, approximately 40% of the population is sensitive to this odor (Lunde, et al, 2012). It is unclear whether the proportion of androstenone-sensitive individuals varies in different countries, but if so, it may impact the areas from which pork products are imported to different countries, with consequential economic considerations (Lunde, et al, 2012).…”
Section: Odormentioning
confidence: 99%
See 1 more Smart Citation
“…The OR7D4 genotype explained 39% and 19% of the variance in intensity rating and perceived pleasantness of these odors, respectively [32]. As androstenone occurs in pork derived from male pig, the OR7D4 genotype is also shown to affect food preference, with subjects carrying the more sensitive OR7D4 variant tending to rate the androstenone-containing meat as less favorable [34]. The OR7D4 genotype is also correlated with the rating of partner odors in heterosexual partners, which in turn associates with scores of anxiety and depression [35].…”
mentioning
confidence: 99%